A fully analog side-band cancellation technique in radio-frequency transmitters. (July 2016) - Nikoofard, Ali; Kananian, Siavash; Hadizadeh, Ehsan; Fotowat-Ahmady, Ali
Abstract: In this paper, a new fully analog technique is proposed by means of which the adverse effects of frequency dependent gain/phase errors in quadrature transmitters are suppressed. Two separate phase and gain mismatch cancellation loops are implemented which search for the minimum side-band component. A new sign detection method is also introduced which makes sure the direction of the loop is correct. Analytical models and mathematical derivations have been presented which corroborates the circuit implementation. A proof of concept prototype using off-the-shelf components have also been measured which suggests 38-dB side-band rejection (SBR). Furthermore, the measured TX EVM and BER are improved by an order of magnitude for a QPSK-modulated input signal.